A new species of the genus Naddia Fauvel, 1867 (Coleoptera: Staphylinidae: Staphylininae) from southern China - He, Liang; Huang, Tian; Schillhammer, Harald; Zhou, Hong-Zhang (Zootaxa, 2023)
This study describes a new rove beetle species, Naddia flavipes sp. nov. from southern China and provides additional morphological knowledge on Naddia hainanensis Yang & Zhou 2010. Line drawings and color illustrations of adult structures and genitalia are provided for both species.